2021
DOI: 10.1002/adma.202105505
|View full text |Cite
|
Sign up to set email alerts
|

Amphipathic Binder Integrating Ultrathin and Highly Ion‐Conductive Sulfide Membrane for Cell‐Level High‐Energy‐Density All‐Solid‐State Batteries

Abstract: Current sulfide solid‐state electrolyte (SE) membranes utilized in all‐solid‐state lithium batteries (ASLBs) have a high thickness (0.5–1.0 mm) and low ion conductance (<25 mS), which limit the cell‐level energy and power densities. Based on ethyl cellulose's unique amphipathic molecular structure, superior thermal stability, and excellent binding capability, this work fabricates a freestanding SE membrane with an ultralow thickness of 47 µm. With ethyl cellulose as an effective disperser and a binder, the Li6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 36 publications
1
57
0
Order By: Relevance
“…The thin SE membrane has a high ionic conductivity of 1.65 mS cm −1 and ultralow areal resistance of 4.32 Ω cm −1 , as reported in our previous work. [35] Two kinds of ASLBs were prepared, in which the mass loadings of cathode were 10 and 20 mg cm −2 . The n/p ratio was ≈1.35, calculated based on the cathode and anode capacities in half cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thin SE membrane has a high ionic conductivity of 1.65 mS cm −1 and ultralow areal resistance of 4.32 Ω cm −1 , as reported in our previous work. [35] Two kinds of ASLBs were prepared, in which the mass loadings of cathode were 10 and 20 mg cm −2 . The n/p ratio was ≈1.35, calculated based on the cathode and anode capacities in half cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thin SE Layer Fabrication: The fabrication of the thin SE layer was reported in the previous work. [35] In detail, 2 mg of ethyl cellulose was dissolved in 2 mL of toluene at 50 °C. After this was stirred for 2 h, 98 mg of Li 6 PS 5 Cl powder was dispersed in the solution with continuous stirring at 300 rpm for 2 h. The dispersion was then cast on a vacuum filtration system with a filter diameter of 4.4 cm.…”
Section: Methodsmentioning
confidence: 99%
“…By controlling the reasonable solid loading (54 wt%) level and binder content (~5 wt%) in the slurry, the ionic conductivity (1.12 mS cm −1 ) of the Li 6 PS 5 Cl film incorporating NBR binders is comparable with that of a commonly cold‐pressing, binder‐free thick pellet (1.10 mS cm −1 ), which indicates that in the case of fewer defects in the SE film and uniform component distribution, the NBR binders have a negligible influence on the ionic blocking of SE membrane. In addition, Cao et al 376 subsequently demonstrated ethyl cellulose with amphipathic molecular structure as a disperser and a binder during SE membrane fabrication entails it discretely distributed inside the SE membrane instead of continuous wrapping, thereby restraining the ionic blocking effect caused by binders.…”
Section: Processing Strategiesmentioning
confidence: 99%
“…Apart from doping of other elements to induce the in situ generation of SEI to suppress the interfacial reaction, the construction of threedimensional and flexible electrolytes can also contain the interfacial reaction. Zhu et al (Cao et al, 2021) synthesized flexible and highly ion-conductive electrolyte films using ethylcellulose and LPSCl. The electrolyte film can fully contact with the lithium metal anode, inhibit the growth of lithium dendrites under high pressure, and its own excellent thermal stability can inhibit the decomposition of the electrolyte film during cycling.…”
Section: Modification Of the Argyrodite Solid-state Electrolytesmentioning
confidence: 99%